The effects of fermented feedstuff derived from Citri Sarcodactylis Fructus by-products on growth performance, intestinal digestive enzyme activity, nutrient utilization, meat quality, gut microbiota, and metabolites of broiler chicken - Zhou, Xinhong; Zhang, Huaidan; Li, Shiyi; Jiang, Yilong; Kang, Lijuan; Deng, Jicheng; Yang, Chuanpeng; Zhao, Xin; Zhao, Jingjing; Jiang, Li; Chen, Xianxin (Frontiers in Veterinary Science, 2023)
This research aimed to assess the impact of fermented Citri Sarcodactylis Fructus by-products (FCSF) on the growth performance, gut digestive enzyme activity, nutrient utilization efficiency, gut microbiota, and their metabolites in broiler chickens. A total of 1080 male broiler chickens were allocated into four groups consisting of 6 replicates per group, each containing 45 chickens. The basal diet was provided to group T1, while groups T2-4 were supplemented with 1%, 3%, and 5% FCSF in the basal diet, respectively. The experimental period was 42 days. The findings revealed that supplementing FCSF improved the FW and ADG of broiler chickens, and led to a reduction in the F/G, ADFI, and mortality rate of broiler chickens (p<0.05). Furthermore, supplementation with 3% and 5% FCSF improved the thigh yield, semi-eviscerated carcass yield, slaughter yield, and lipase activity in the duodenum and ileum of birds (p<0.05). Additionally, supplementing 3% FCSF enhanced the activity of protease in the duodenum of broilers (p<0.05). Moreover, supplementing 3% FCSF enhanced the utilization of total phosphorus, dry matter, crude protein, and crude ash in the feed by broilers (p<0.05).Supplementing 1% FCSF significantly increased the C14:0, C14:1, and C20:1 content in the breast meat compared to the other experimental groups (p<0.05). The levels of C20:4n6 and C23:0 in the breast meat of birds of FCSF supplemented groups were lower than in T1 (p<0.05). Furthermore, the content of ∑ω-3PUFA decreased after supplementing with 3% and 5% FCSF (p<0.05). 16SrDNA showed that supplementing 3% FCSF reduced the ACE, Chao1, and Shannon indices in the cecum of birds (p<0.05). Supplementing 3% FCSF also decreased the abundance of the phylum Desulfobacterota and improved genera Coprobacter and Prevotella in the cecum of broiler chickens (p<0.05). Metabolomic analysis of the gut microbiota revealed that supplementing 3% FCSF upregulated 6 metabolites and downregulated 16 metabolites (p<0.05). Moreover, supplementing 3% FCSF downregulated 12 metabolic pathways and upregulated 3 metabolic pathways (p<0.05). In summary our findings indicate that supplementing FCSF can improve the growth performance of broiler chickens by enhancing intestinal digestive enzyme activity, nutrient utilization, improving gut microbial diversity, and influencing the metabolism of gut microbiota.